Desentralisasi sebagai Upaya Pembangunan Desa secara Menyeluruh Menurut UU No. 6 Tahun 2014 - Khoiriza N., Muhammad (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2016)
Various regulations have been issued by the government to develop the village since 1948 by Law No. 22 on Local Government. The final rule is Law No. 6 of 2014 on the Village. The genesis of Law No. 6 of 2014 is the embodiment of a decentralized system. This paper intends to explain how the decentralization system provided by Law No. 6 of 2014 gives effect to undertake rural development as a whole. Through this legislation anyway been delegated from thecentral state to local governments to lead to the village government can be realized. With the delegation of authority from the central government to village government, the village government has the power to manage all matters relating to his village and ended up giving a significant influence in the development of the village. Nevertheless, the overall rural development may occur when leader and staff of the village can create policies that impact on rural development which is determined according to the priorities in the Minister of Rural No.5 of 2015.